The Effect of Alcohol Consumption on Tear Production in Young Adults: Using Smirnoff Ice as a Case Study - E., Odjimogho Stella; S., Odjimogho Emoefe; I., Uyi Charity; O., Gabriel Benjamin (Darul Yasin Al Sys, 2025)
Alcohol is a depressant that interferes with tear production, disrupting its balance and leading to insufficient eye lubrication and gradual onset of dry eyes. To determine the effect of alcohol on tear production. Eighty (80) eyes of 40 healthy subjects between 18-30 years. The baseline measurement of the mean tear production was taken with Schirmer tear strip before the commencement of the work. The subject ingested a bottle of Smirnoff ice drink (33 cl volume with 5.5% alcohol). The mean tear production was then measured at 30, 60 and 90-minutes intervals. The mean value before the intake of alcohol and 30, 60, and 90-minutes intervals after the intake in both eyes (OD and OS) were measured. The baseline value for OD was 24.05±6.41, which increased to 26.88±7.43 in 30 minutes. Thereafter, the value decreased to 25.93±6.64 and 25.58±6.22 respectively at 60 and 90 minutes intervals. The baseline value for OS was 23.13±6.62 and this also increased to 26.13±7.45, 30 minutes after intake; and 24.78±6.65 and 24.88±6.51 respectively at 60 and 90 minutes intervals. Alcohol intake has an effect on tear production leading dry eyes syndrome.